Tessituras de memória em Quarto de despejo: diário de uma favelada, de Carolina Maria de Jesus - Pereira, Ana Cleia Silva (2023)
Starting from the perspective that literature uses memory as a inspiration source to represent reality in its fictional plots, the present work analyzes the social cultural exclusion and their individual and collective memories in the literary work Quarto de Despejo: Diário de uma favelada (1960 [2014]), from Carolina Maria de Jesus (1914-1977). Having as background the representation of a memory that transcends the subjective, the book, built as a diary, registers the daily of Carolina in the Favela do Canindé, in São Paulo, where she and her children lived most of their life. From her reports, the writer exposes her experience as a scavenger and the misery situation of the favela’s residents, beyond that, she strongly criticizes society, and stands in front of her condition as a subordinate. Supported in this information to make this investigation we adopted as methodology the bibliography research of qualitative nature, in which we discuss the thematic according to literary studies. In this perspective, as for the memorial debate the work builds itself in the ideas from authors such as Halbwachs (2013), Le Goff (2013), Ricoeur (2010) and Assmann (2011); in the field of literature the research came from the discussion of Bakhtin (1997) Farias (2017), Dalcastagné (2012), Resende (2008) and others. Having in sight that the route of analyzes from the work in study it will be possible to perceive that the individual memory registered in Quarto de Despejo (1960 [2014]) has collective implications, once that past and present talk through historical questions.